Pembangunan Berbasis Perdesaan Melalui Pemekaran Wilayah Kabupaten Garut Selatan - Dadang, Asep (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One of the current development concepts is to use Regional Autonomy (decentralization) through policy Number 32 of 2004. This policy tries to determine how development is based on the wishes of the community, whether the community is capable of managing its area in development or vice versa. Community-based development (people centered development) is a democratic development model and enlivens the atmosphere of development at the grassroots. In this way, it is hoped that this pattern can improve various problems that occur among the community, realizing local wisdom, so that the maturity of the community in development will be visible and have the effect of strengthening unity and cohesion.